Randomized, double-blind, three-arm, parallel-group study to compare the efficacy and safety of a single dose of 100 and 200 mg of mifepristone for cervical ripening in term pregnancies - Orozco, Leonardo J.; Guerrero, Silvia; Rosales, Mixel J.; Ramos, Jose S. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Mifepristone is an antiprogestin developed to antagonize the action of progesterone by inhibiting its receptors. It has had a recognized role in the medical termination of early pregnancy, reduction in the volume of uterine fibroids and endometriosis symptoms. A new indication for labor induction and cervical ripening in has been proposed. The objective was to compare the efficacy and safety of mifepristone 100 and 200 mg with placebo for cervical ripening in term pregnancies. Methods: Double-blind, placebo-controlled trial of 90 term pregnancy women randomly assigned to receive orally tablet of 100 mg and 200 mg mifepristone or placebo. Efficacy was assessed by measuring changes in cervical ripening according to Bishop 72 hours after treatment. Statistical analysis was using the t-student test and the chi-square test. The relative risk (RR) was determined with a 95% confidence interval. Results: The bishop score and the number of contractions at 48 hours in the group of 200mg of mifepristone presented a significantly higher mean value in relation to the placebo (p=0.04). At 72 hours, cervical length showed a significant difference (p<0.01) in both mifepristone groups compared to the placebo group. Also, at 72 hours a significant increase in the mean duration of contractions was demonstrated in the 100 mg mifepristone group. Conclusions: There was a significant increase in Bishop’s score for the 200 mg mifepristone group probably due to a significant increase in contractions at 24 hours. No differences were observed between groups in adverse events.